N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) predicts the cardio‐renal response to aliskiren in patients with type 2 diabetes at high renal and cardiovascular risk. Issue 12 (5th August 2018) - Idzerda, Nienke M. A.; Persson, Frederik; Pena, Michelle J.; Brenner, Barry M.; Brunel, Patrick; Chaturvedi, Nish; McMurray, John J.; Parving, Hans‐Henrik; de Zeeuw, Dick; Heerspink, Hiddo J. L.
Abstract : Sodium retention and volume overload are the main determinants of poor response to renin‐angiotensin‐aldosterone system (RAAS) inhibition in patients with diabetes. As volume excess can exist without symptoms, biomarkers are needed to identify a priori which patients are volume overloaded and may experience less benefit from RAAS inhibition. N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) is released in the setting of increased cardiac wall stress and volume overload. We conducted a post hoc analysis among 5081 patients with type 2 diabetes mellitus participating in the ALTITUDE trial to investigate whether NTproBNP can predict the effects of additional therapy with aliskiren on cardio‐renal endpoints. Aliskiren compared to placebo reduced the risk of the primary cardio‐renal endpoint events by 20% (95% confidence interval [CI] 16 to 61) and 2% (95% CI –42 to 30) in the two lowest NT‐proBNP tertiles, and it increased the risk by 25% (95% CI –4 to 96) in the highest NT‐proBNP tertile ( P value for trend = 0.009). Similar trends were observed for the cardiovascular and end‐stage renal disease endpoints. Effects of aliskiren compared to placebo on safety outcomes (hyperkalaemia and hospitalization for acute kidney injury) were independent of NT‐proBNP. In conclusion, baseline NT‐proBNP may be used as a marker to predict the response to aliskiren with regard to cardio‐renal outcomes when added to standard therapy with RAAS inhibition.